PENGARUH KUALITAS AUDIT, LIKUIDITAS, SOLVABILITAS, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Abdullah Syafii, - (2020)
The study purposes to determine how audit quality, liquidity, solvability and prior year audit opinion  in affecting the acceptance of going concern audit opinion on the companies listed in Indonesian Stock Exchange in 2018-2019. The research methods that used in this research is causal verification method. The population of this research is companies listed in Indonesian Stock Exchange since 2018 until 2019, while for sampling used purposive sampling method. The data used was secondary data that was collected by documentation technique. In analyzing the data, this study used logistic regression statistical test. Based on the calculation of regression logistic analysis generated that the prior year audit opinion had an effect on the acceptance of going concern audit opinion, while audit quality, liquidity and solvability had no effect on the acceptance of going concern audit opinion.